Heavy metals contamination in edible vegetables from several farmlands in Sarawak - Nur Aa'In Mazura, bt. Che Mahtar (Universiti Malaysia Sarawak (UNIMAS), 2006)
Vegetables provide the human body with the essential bioavailable trace elements, and a constant supply of these various elements is necessary and highly recommended for daily life. Various vegetables species were collected from two different farmlands; Beratok and Siburan.The vegetables collected from Beratok were kale, green mustard, and white mustard whereas green mustard, mustard, cucumber and long bean were collected from Siburan farmland. Fe, Co, Mn, Zn, Cu and Pb were determined in different parts of vegetables (leaves, stems and roots) using two different method; wet digestion and dry ashing. The leafy vegetables showed great ability to accumulate the micronutrients (Fe, Zn and Mn) in higher level than the fruity vegetables. Both fannlands revealed higher accumulation of Pb for both digestion methods which did not comply with FAOIWHO and Food Act 1983 guidelines. There was no significant difference (P>O.05) between the two methods; dry ashing and wet digestion method.